2010
DOI: 10.1021/cm9018474
|View full text |Cite
|
Sign up to set email alerts
|

Pt Alloy and Intermetallic Phases with V, Cr, Mn, Ni, and Cu: Synthesis As Nanomaterials and Possible Applications As Fuel Cell Catalysts

Abstract: Nanomaterials as catalysts for fuel cells are not only highly desirable, but necessary to reach the high reaction rates (or power densities) demanded by many applications. The exploration of catalyst materials beyond Pt metal, such as Pt containing alloys and intermetallics, immediately leads to significant synthetic challenges to prepare nanoparticles with controlled composition, structure, and morphology. To facilitate a comprehensive study of these materials, a generalized synthetic approach is desirable. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 35 publications
1
64
1
1
Order By: Relevance
“…In addition, different from random alloys, ordered intermetallic nanocrystals offer predictable control over structural, geometric, electronic, and ensemble effects. The last two decades have witnessed the successful synthesis of Pt‐based intermetallic nanocrystals through the incorporation of oxyphilic metals such as Ti, V, Nb, Ta, Cr, Mn, Fe, Co, Ni, Cu, Ag, Zn, In, Sn, Pb, Sb, and Bi, toward the oxidation of fuel with enhanced catalytic properties …”
Section: Catalytic Applications Of Intermetallic Nanocrystalsmentioning
confidence: 99%
“…In addition, different from random alloys, ordered intermetallic nanocrystals offer predictable control over structural, geometric, electronic, and ensemble effects. The last two decades have witnessed the successful synthesis of Pt‐based intermetallic nanocrystals through the incorporation of oxyphilic metals such as Ti, V, Nb, Ta, Cr, Mn, Fe, Co, Ni, Cu, Ag, Zn, In, Sn, Pb, Sb, and Bi, toward the oxidation of fuel with enhanced catalytic properties …”
Section: Catalytic Applications Of Intermetallic Nanocrystalsmentioning
confidence: 99%
“…Pt is the most commonly used electrocatalyst for both cathodic and anodic reaction in the commercial fuel cells. Pt is an expensive element and the efforts to reduce Pt and other noble metal contents in fuel cells are challenging [11][12][13][14]. On the other hand, the new non-noble metal catalysts have shown a low mass activity in fuel cells [3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Intermetallic compounds, which are atomically ordered alloys that tend to have well-defined compositions and crystal structures that differ from those of their constituent elements, have been used as catalysts for quite some time for chemical transformations such as hydrogenation, ammonia synthesis, methanol synthesis and methanol oxidation [19]. In particular, recent work has shown that intermetallic alloys are potential candidates for catalysis in the electrochemical oxidation of small organic molecules (SOMs) because of their increased current densities and their improved resistance to CO poisoning [20][21][22][23]. Roychowdhury et al [24] prepared the ordered intermetallic compounds PtBi and PtPb using anhydrous methanol as the solvent and sodium borohydride as the reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Miura et al [28] synthesized the intermetallic PtZn nanoparticles with stable and high activities toward formic acid and methanol electrooxidation. Ghosh et al [22] have been able to demonstrate synthesis of several phases (both alloy and ordered intermetallics for binary Pt-V/Mn/Cr/Ni/Cu systems) that rarely, if ever, have been synthesized as nanomaterials without using surfactants. Additionally, they have shown that some of these materials are active catalysts, with activity superior to Pt for formic acid oxidation.…”
Section: Introductionmentioning
confidence: 99%